Explorations and Excavations in Turkey, 1964 - Alkım, Handan
Fortsetzung von 27:d:11a; 1. The Cave of Karain (Antalya); 2. The Cave of Kediini (Alanya-Antalya); 3. Ünye (Ordu); 4. Prehistoric Explorations (Regions of Marmara and Thrace): The cave of Yarımburgaz. The environs of Terkos Lake. Kanallıköprü Hüyük (Silivri). The Neighbourhood of Istanbul; 5. Central Anatolian Survey; 6. Suberde (Konya); 7. Can Hasan (Konya); 8. Explorations and excavations in Urfa-Diyarbakır-Siirt areas; 9. Koçumbeli (Ankara); 10. Exploration and Excavations in the District of Islâhiye (Gaziantep): Tilmen Hüyük. Gedikli (Karahüyük); 11. Karataş-Semayük (Antalya); 12. Çavdarlıtepe (Afyon); 13. Müsgebi (Muğla); 14. Kültepe (Kayseri); 15. Acem Hüyük (Aksaray-Niğde); 16. Kara Hüyük (Konya); 17. Boğazköy (Çorum); 18. Alaca Hüyük (Çorum); 19. Ilıca (Ankara); 20. Aslantepe (Malatya); 21. Historical-Geographical Investigations in Central and Southern Anatolia; 22. Survey in the Vilayet of Muş: 23. Altıntepe (Erzincan); 24. Kef Kalesi (Adilcevaz-Bitlis); 25. Harmantepe Necropolis (Adilcevaz-Bitlis); 26. Patnos (Karaköse/Ağrı); 27. Ani (Kars); 28. Çavuştepe (Van); 29. Karatepe und Kadirli (Adana). Kadirli-Alacami; 30. Yalıncak (Ankara); 31. Sardis (Manisa); Der Rest des Berichtes behandelt klassische Ausgrabungsstätten.